Ativos Intangíveis: o uso das técnicas de valuation para a transferência de tecnologia - Silva, Felipe Eduardo de Oliveira (2024)
This research analyzes how scientific knowledge and technological innovations, especially those originating in universities, have become consolidated as driving forces for sustainable development, by integrating social, economic, and environmental benefits. Scientific production generates intangible assets that confer competitive advantages to organizations. In this sense, Technology Transfer process needs to ensure a more accurate valuation of these patents, identifying the need to apply appropriate valuation techniques. The objective of this study is to use the Discounted Cash Flow and the Real Options Theory, through the Black-Scholes model, to perform the valuation of a 3D printer intended for the manufacture of metal parts, which employs the quasi-immersion thermal cooling technique. The methodology consisted of applying the Discounted Cash Flow together with the Black-Scholes method, with the purpose of evaluating whether the Discounted Cash Flow is the most effective technique in the context of valuation in Technology Transfer processes. The results showed that Discounted Cash Flow, which is a static method, does not demonstrate assertiveness in predicting future cash flows and operational performance. On the other hand, the Black-Scholes model reflects the volatility of option prices in short periods, providing investors with a delta hedge strategy, which is essential for mitigating price fluctuations in market contexts.